Biochemical and haematological reference intervals for 3–4-week-old kiwi chicks (Apteryx mantelli) reared in captivity - Scheltema EM; Howe L; Pickard KMO; Fletcher MC; Gartrell BD; Singh PM; Morgan KJ (Taylor and Francis Group, 2025)
Aims: To establish biochemical and haematological 95% reference intervals (RI) for juvenile North Island brown kiwi (Apteryx mantelli) chicks using parametric analysis. Methods: Blood samples were collected from healthy 3–4-week-old, captive-reared North Island brown kiwi chicks (n = 32; male = 19, female = 13). Concentrations of total plasma protein (TPP), uric acid, glucose, phosphorus, calcium, albumin, globulin, potassium, and sodium and activities of aspartate aminotransferase and creatine kinase (CK) were measured using an automated VetScan VS2 laboratory analyser and the Abaxis Avian-Reptilian Profile Plus. Total and differential white blood cell counts were determined manually on blood smears prepared with a modified Wright-Giemsa stain. TPP was also measured manually using a refractometer, and packed cell volume (PCV) was measured using microhaematocrit tubes. RI were calculated using parametric and non-parametric methods depending on the distribution of the data. Confidence intervals (90%) around upper and lower bounds of the RI were calculated to assess certainty of the intervals. Results: Biochemical (n = 28; male = 17; female = 11) and haematological (n = 22; male = 14, female = 8) 95% RI were generated for juvenile North Island brown kiwi. The 90% CI of the upper or lower limits of the majority of the RI generated were > 0.2 times the RI, reflecting the relatively small sample size. There was no evidence of a difference in mean biochemical values collected from sedated vs. un-sedated, and male vs. female chicks. However, the concentration of phosphorus was higher (p = 0.034) in samples that were analysed > 1 hour after collection (2.097 (SD 0.202) mmol/L) compared to samples analysed < 1 hour after collection (1.856 (SD 0.349) mmol/L). Conclusions: This data provides the first comprehensive biochemical and haematological RI generated for Apteryx spp. chicks carried out under uniform collection and sample handling protocols, making the results robust and applicable to other captive-reared kiwi chicks. Clinical relevance: In comparison to published RI from adult kiwi (Doneley 2006; Morgan 2008), kiwi chicks in this study had lower PCV, TPP and uric acid concentrations, and higher CK activities, white cell counts and lymphocyte counts. These RI are of value to wildlife veterinarians and conservation managers assessing the health of individual kiwi chicks, and for population-level comparison of birds of different ages and living in different managed or wild habitats.
Keywords: Kiwi; reference interval; Apteryx spp; haematology; biochemistry